Tingkat Kreativitas Siswa SD yang Memiliki Disposisi Matematis Rendah Dalam Memecahkan Masalah Matematika: The Creativity Level of Elementary Students Who Have Low Mathematical Dispositions in Solving Mathematical Problems - Afifah, Dian Septi Nur (Universitas Muhammadiyah Sidoarjo, 2018)
This research aims to describe student’s level of creativity that have low mathematic disposition in math problem solving. This researchis qualitative research. Researcher as the main instrument. While instruments that use in this study are student’s mathematic disposition questionnaire, test of mathematic problems solving and guidelines for interviews. Data collection are questionnaire, test, and interview. The analysis data used are data reduction, data displayed, and conclusions. The use triangulation to check the validity of the data. The results of this research that the level of creativity of elementary school students who have a low disposition is the level of creativity 0. For that required a learning strategy that can improve students' mathematical disposition in order to solve math problems. So mathematical disposition affects the ability of elementary students in solving mathematical problems.